An unprecedented base-promoted domino reaction of methyleneindolinones and N-tosyloxycarbamates for the construction of bispirooxindoles and spiroaziridine oxindoles1. Issue 53 (7th July 2015) - Wang, Qi-Lin; Cai, Tian; Zhou, Jing; Tian, Fang; Xu, Xiao-Ying; Wang, Li-Xin
<x xml:space="preserve">Abstract</x> An efficient and unprecedented domino reaction of methyleneindolinones and N-tosyloxycarbamates was realized to construct bispirooxindoles and spirooxindole aziridines.